Van de passielooze lelie - Eeden, Frederik van 1860-1932 (Amsterdam Versluys, 1901)
In the collection of poetry 'Van de passielooze lelie' (1901), Frederik van Eeden expressed his desire to merge with God through suffering and agony, as he makes himself known in music, nature and selfless love. Critics were divided over this collection: according to De Amsterdammer, Van Eeden was half apostle and half minister, but Den Gulden Winckel called him a great poet and an exalted mystic.
See also 09E03
waarbij zijn opgenomen de "enkele verzen"
Keywords: 20th Century (1901-2000); Poetry; Netherlands